2023
DOI: 10.18502/npt.v10i1.12256
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing foot care behavior among patients with type 2 diabetes mellitus who have a high-risk diabetic foot in China

Abstract: Background & Aim: Foot ulceration and amputation have increased significantly among Chinese patients with type 2 diabetes mellitus. Proper foot care behavior is an important strategy for reducing the risk of diabetes-related foot issues. The current study aimed to assess foot care behavior and its influencing factors, including self-efficacy, foot care knowledge, and social support, among patients with type 2 diabetes mellitus who have a high-risk diabetic foot in Wenzhou, China. Methods & Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings are consistent with existing literature. 21,22 Perceived Social Support Level in T2DM Patients…”
Section: Diabetes Self-management Behavior Level In T2dm Patientsmentioning
confidence: 99%
“…These findings are consistent with existing literature. 21,22 Perceived Social Support Level in T2DM Patients…”
Section: Diabetes Self-management Behavior Level In T2dm Patientsmentioning
confidence: 99%
“…It is necessary to design an application that, apart from improving foot care behavior, also increases selfefficacy and provides regular foot care education as previously developed (Cheng et al, 2023). Even though social and psychological aspects have been developed, effective applications have been developed in providing information and increasing self-efficacy, self-care and motivation for diabetes sufferers, but they still need development and integration with other aspects (Mufidah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other research emphasizes that further development, refinement and testing of applications on smartphones to increase self-efficacy and reduce the risk of diabetic foot is necessary (Kilic & Karadağ, 2020). Other research also revealed that interventions that focus on increasing self-efficacy will change diabetic foot care behavior (Cheng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%